AXDND1, a novel testis-enriched gene, is required for spermiogenesis and male fertility - Qian Ma (Nature Publishing Group, 2021)
Abstract Spermiogenesis is a complex process depending on the sophisticated coordination of a myriad of testis-enriched gene regulations. The regulatory pathways that coordinate this process are not well understood, and we demonstrate here that AXDND1, as a novel testis-enriched gene is essential for spermiogenesis and male fertility. AXDND1 is exclusively expressed in the round and elongating spermatids in humans and mice. We identified two potentially deleterious mutations of AXDND1 unique to non‐obstructive azoospermia (NOA) patients through selected exonic sequencing. Importantly, Axdnd1 knockout males are sterile with reduced testis size caused by increased germ cell apoptosis and sloughing, exhibiting phenotypes consistent with oligoasthenoteratozoospermia. Axdnd1 mutated late spermatids showed head deformation, outer doublet microtubules deficiency in the axoneme, and loss of corresponding accessory structures, including outer dense fiber (ODF) and mitochondria sheath. These phenotypes were probably due to the perturbed behavior of the manchette, a dynamic structure where AXDND1 was localized. Our findings establish AXDND1 as a novel testis-enrich gene essential for spermiogenesis and male fertility probably by regulating the manchette dynamics, spermatid head shaping, sperm flagellum assembly.